2020
DOI: 10.1007/s40544-020-0414-z
|View full text |Cite
|
Sign up to set email alerts
|

Micro/atomic-scale vibration induced superlubricity

Abstract: With the rapid development of industry, the inconsistency between the rapid increase in energy consumption and the shortage of resources is becoming significant. Friction is one of the main causes of energy consumption; thus, the emergence of superlubricity technology can substantially improve the energy efficiency in motion systems. In this study, an efficient method to control superlubricity at the atomic-scale is proposed. The method employs vibrational excitation, which is called vibration induced superlub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Then efficient methods to control superlubricity by external vibration conditions have been developed [42]. The energy dissipation in the tapping mode seems to be deeply related to the vibration induced superlubricity due to the similar motion patterns [43].…”
Section: Introductionmentioning
confidence: 99%
“…Then efficient methods to control superlubricity by external vibration conditions have been developed [42]. The energy dissipation in the tapping mode seems to be deeply related to the vibration induced superlubricity due to the similar motion patterns [43].…”
Section: Introductionmentioning
confidence: 99%
“…With the in-situ TEM nanofriction tests in high vacuum, the external environmental effects were eliminated, the tip was driven by a cantilever to slide with the surface of sp 2 nanocrystallited carbon films, which is similar with the AFM friction. In the atomic scale, the Prandtl-Tomlinson (P-T) model dominate the understanding of stick-slip [39][40][41]. In this research, a minimum force to the slider for the "pretensioning" of the spring between point mass and slider was also needed to overcome potential barriers, as the first friction force increasing stage in this manuscript.…”
Section: In-situ Tem Nanofriction Propertiesmentioning
confidence: 96%
“…Previous experiments and simulations [12,22,27,28] have suggested that vibration-induced friction reduction is dependent on the magnitude of vibration amplitude. This is also consistent with the results shown in Fig.…”
Section: Friction Vs Actuation Amplitudementioning
confidence: 97%
“…Using atomic force microscopy (AFM), Socoliuc et al [12] showed that, by imposing an alternating current (AC) voltage between a conductive probe and an ionic crystal, friction could be substantially reduced owing to vibration caused by alternating electrostatic force. Similar friction modulation has also been achieved by directly vibrating the base of the AFM probe [20,21], or the sample using external transducers [22][23][24][25][26]. The effect of mechanical vibration on microscopic friction is commonly understood by the modified Prandtl-Tomlinson (P-T) model [27][28][29], where the mechanical vibration is considered as a perturbation to the interaction corrugation associated with sliding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation